REFIX layer in children with MIH: Thickness, color, and hypersensitivity, a preliminary longitudinal study using an intraoral scanner - Ana Carolina Cheron Gentile; Giovanna Bueno Marinho; Bruna Cordeiro Amarante; Ana Clara Moronte Dias de Souza; Vanessa Silva da Costa; Fabiano Vieira Vilhena; Marcelo Bönecker (Journal of Applied Biomaterials & Functional Materials, 2025)
Teeth with molar-incisor hypomineralization (MIH) present demarcated opacities, which are structural alterations in the enamel, making them more porous and often resulting in dentin hypersensitivity (DH). New technologies have been developed for the management of MIH-affected teeth, including bioactive silicon materials, which could form new silicon-enriched hydroxyapatite crystals, reinforcing the structure, and acting as an obliterating agent. The aim of this study was to evaluate the formation of a mineral layer and changes in the demarcated opacities’ color employing an intraoral Trios 4 scanner after using a new silicon-based bioactive clinical system plus calcium in 11 children with MIH. DH was assessed with the VAS and SCASS scales at baseline, 15, and 30 days. Intraoral scanning revealed the formation of a mineral layer after 30 days, and significant DH reduction was observed (mean reductions: VAS 65% at 15 days and 83% at 30 days; SCASS 76% at 15 days and 94% at 30 days). Moreover, Cox regression analysis identified baseline pain severity as an independent predictor of a faster reduction in DH (adjusted HR = 0.06, p  < 0.05). Color analysis suggested a lightening of the demarcated opacities. These results indicate that the new silicon-based bioactive clinical system plus calcium may effectively reduce DH and modify both enamel structure and opacity coloration in MIH-affected teeth. Longitudinal studies with larger samples are needed to assess the long-term effects.